Analysis of Treatment Compliance Factors in Type 2 Diabetes Mellitus Patients - Desia, Maya; Yetti, Husna; Lestari, Yuniar (Journal La Medihealtico, 2025)
Non-compliance with taking medication in DM patients can reduce a person's quality of life and become the main cause of a number of microvascular problems. Therefore, complex problems related to diabetes are one of the global health problems that must be addressed immediately. The purpose of this study was to determine the factors related to medication compliance in type 2 DM patients. This study used a mixed method study approach or a combination of two types of research, namely quantitative research and qualitative research. The type of mixed method research design used is explanatory sequential design. The sampling method in this study was by proportional sampling. Furthermore, to determine the target sample, a simple random block sampling technique was used, namely 347 DM patients. The results of the analysis showed no significant relationship between gender p-value = 1,000 (> 0.05), education p-value = 0.232 (>, 0.05), knowledge p-value = 0.076 (> 0.05), dxuration of suffering p-value = 0.162 (> 0.05), belief p-value = 0.680 (> 0.05), access to health services p-value = 0.602 (> 0.05), and there was a significant relationship between family support and DM treatment compliance with p-value = 0.020 (<0.05). The conclusion of this study is that more than half of DM patients have low treatment compliance, are female, have low education, have a duration of <5 years, have access to health that takes a long time, and lack of family support. More than half of DM patients have high knowledge and positive beliefs.